Pendekatan Sosial dan Geografis dalam Penetapan Batas Dusun Pintu Angin dan Dusun Bonou - Mariati, Sari; Alzura, Yuniza; Utami, Hana Fitri Indrayati; Fitri, Nofila; Hedriansyah, Muhammad Aditya; Azizah, Hiska Nasra; Kurniawan, Rendi; Aldiasep, Faldo; Adinda, Najla Sukma; Akbar, Decka Imama Patria (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
Determination of boundaries between hamlets is a complex process, involving various social and geographical aspects, and requires a participatory approach to ensure fairness for all parties involved. This article examines the process of delimiting the boundaries between Pintu Angin Hamlet and Bonou Hamlet with a focus on the social and geographical approaches applied in resolving boundary conflicts. The process begins with the identification of problems that include unclear physical boundaries, land use disputes, and differences in social and cultural perspectives. Furthermore, the implementation method involves socialization, field surveys, and boundary determination through discussions involving the local community, with the important role of the Hamlet Head as a mediator. The results of this process indicate that clear boundary determination can reduce social conflict, improve natural resource utilization, and strengthen social relations between hamlets. The implications of this boundary determination include better organized area management, strengthening community participation, and stability of government administration. This article concludes that a holistic approach based on community cooperation is essential in determining fair and sustainable boundaries.